Hypothenar hammer syndrome: case report and literature review() - Queiroz, Márcia Maria Muniz de (Rev Bras Ortop, 2013)
Case report of a 69 year-old patient, with history of repetitive trauma events in the wrist, clinically simulating tenosynovitis, being held with Doppler Ultrasound and Magnetic Nuclear Resonance, which showed ulnar artery thrombosis. The accurate diagnosis of the hammer hypothenar disease through those tests enable an early intervention, improving the prognosis of patients affected by this rare disease.